2008
DOI: 10.4141/cjps07159
|View full text |Cite
|
Sign up to set email alerts
|

A review of wheat cultivars grown in the Canadian prairies

Abstract: Wheat is Canada's largest crop with most of the production in the western Canadian prairie provinces of Manitoba, Saskatchewan and Alberta. Since wheat production started in western Canada, over 100 yr ago, market classes of hexaploid spring bread wheat (Triticum aestivum L.) were the dominant type of wheat, although production of durum wheat [Triticum turgidum L. ssp. durum (Desf.) Husn.)] has grown significantly over this period, and hexaploid winter wheat was grown on a relatively small portion of the wheat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
105
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(108 citation statements)
references
References 91 publications
1
105
0
2
Order By: Relevance
“…After proving drought and rust resistant in controlled tests, several durum introductions diffused rapidly in Minnesota and the Dakotas (13,22). Table 1, which lists a number of important new wheat cultivars, hints at the growing importance of public breeding (18,23,24). (The distinction between the public and private sectors is not precise, because breeders in both sectors use germplasm from the other.)…”
Section: Resultsmentioning
confidence: 99%
“…After proving drought and rust resistant in controlled tests, several durum introductions diffused rapidly in Minnesota and the Dakotas (13,22). Table 1, which lists a number of important new wheat cultivars, hints at the growing importance of public breeding (18,23,24). (The distinction between the public and private sectors is not precise, because breeders in both sectors use germplasm from the other.)…”
Section: Resultsmentioning
confidence: 99%
“…Glenlea was the only Canadian extra strong wheat grown in the trial. Glenlea is generally characterized as having medium protein content and stronger gluten than the other cultivars studied [34]. Recently, it was reported that the introduction of semi-dwarf high-yielding cultivars has coincided with a decrease in wheat grain Cu, Zn, Fe and Mg contents [35].…”
Section: Discussionmentioning
confidence: 99%
“…McKenzie had 12.7% higher grain yield than the highest yielding check in the test and similar grain protein concentration and resistance to most diseases at the time of registration. McKenzie has the gene Lr21 which confers resistance to prevalent races of leaf rust (McCallum & DePauw 2008 (DePauw et al 2005). Lillian has a solid stem which confers resistance to wheat stem sawfly (Cephus cinctus Nort.…”
Section: Canada Western Red Spring (Cwrs) Doubled Haploid Cultivarsmentioning
confidence: 99%